West Nile Fever in the Russian Federation in 2024, Forecast for 2025 - E. V. Putintseva; S. K. Udovichenko; D. N. Nikitin; N. V. Boroday; A. Yu. Koloskova; A. S. Antonov; O. S. Bondareva; A. V. Toporkov (Проблемы особо опасных инфекций)
The epidemiological situation on West Nile fever (WNF) in the Russian Federation in 2024 was characterized by an increase in the morbidity rate (0.30 cases per 100 thousand population) by 2.6 times compared to the long-term annual average value (0.11) and by 2.1 times compared to the 2023 indicator (0.14). Cases of the disease were registered in 38 constituent entities of Russia, which is the highest value for the entire observation period. Of the administrative territories, where cases of the disease were laboratory-confirmed in 2024, local cases of WNF were officially registered for the first time in 9 constituent entities. Other features of the 2024 season include an increase in the case fatality rate, which exceeded the long-term average in Russia (5.7 % and 3.1 %, respectively), as well as the early start of registration of the first local cases of West Nile virus (WNV) infection. The incidence and clinical course structure of WNF in 2024 did not differ significantly compared to the average long-term values and those in 2023. Active detection of WNF in groups of patients with fever and other similar manifestations of the disease was organized in 62 constituent entities in 2024. Increased efficiency of morbidity monitoring was observed in certain entities of the Southern, North Caucasian and Volga Federal Districts. The study of the cohort that is immune to WNV among the healthy population in 2024 was conducted in 69 entities of Russia. Monitoring of infection of WNV hosts and vectors was carried out in 79 constituent entities; the activity of the epizootic process was established in 19 administrative territories. In 2024, WNV lineage 2, the population of which is characterized by genetic heterogeneity, predominantly circulated in the European part of Russia. Single findings of WNV lineage 1 (Rostov Region) and lineage 4 (Volgograd Region) were detected. A quantitative forecast of the development of the epidemiological situation on WNF was developed for entities with the sustained circulation of WNV.